The Effect Of Transformational Leadership Style And Work Motivation On The Performance Of Production Cooperative Members In The Digital Age With Job Satisfaction As An Intervening Variable (A Study Of Production Cooperatives In Agricultural Plantations In - Angga Atmawardhana; Sari Sakarina; Rosalina Febrica Mayasari (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2026)
This study aims to analyze the influence of transformational leadership style and work motivation on member performance in Plantation Production Cooperatives in Banyuasin Regency, with job satisfaction as an intervening variable. The phenomenon of performance in cooperative organizations is crucial to study in order to understand how the role of leadership and internal motivation of employees can optimize organizational productivity. The research method used is quantitative with a population of 100 cooperative members. The sampling technique uses saturated sampling (census), where all members of the population are respondents. Primary data were collected through questionnaires and analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS). The results show that transformational leadership style and work motivation have a positive and significant effect on job satisfaction. Furthermore, job satisfaction is proven to play a significant role as a mediating variable in linking leadership style and motivation to member performance. Statistical findings show the $R^2$ value for the job satisfaction variable of 0.975, which indicates that 97.5% of the variance in job satisfaction is explained by this model. Meanwhile, the R2 value for member performance reached 0.992, indicating that leadership style, motivation, and job satisfaction simultaneously explained 99.2% of the variance in member performance, while the remaining 0.8% was influenced by factors outside the research model. This study recommends enhancing aspects of transformational leadership to strengthen job satisfaction, which will ultimately maximize sustainable organizational performance.